Development of 3D indoor positioning and navigation system - Zhong, Peixiang (2016)
As the age of Internet of Things comes, the location and context based services and applications become increasingly popular. These services and applications have already been applied in many existing scenarios such as emergence evacuation, museums and shopping malls.